Implementation of The Online Single Submission Risk-Based Approach (OSS RBA) Policy In The City of Cirebon - Nur Hanifah; Yanto Heryanto (ann4publisher@gmail.com, 2026)
Background. Digital transformation is driving the government to provide licensing services that are faster, more accountable, and more transparent through the Online Single Submission Risk-Based Approach (OSS RBA) system. However, at the local level, the implementation still faces numerous challenges. Aims. This study has the aim to analyze the implementation of the OSS RBA policy at the DPMPTSP of Cirebon City using the policy implementation theory by George C. Edward III, which puts an emphasis on the aspects of resources, communication, disposition, as well as bureaucracy. Methods. A qualitative approach is used in this study. The study’s results reveal that internal communication functions fairly well, personnel and facility resources are adequate, and implementers' attitudes show a commitment to service. The bureaucratic structure is also supported by clear Standard Operating Procedures (SOPs). Result. The implementation, however, has not been optimal due to ongoing technical disruptions in the centralized system, limited public digital literacy, and the need for coordination with other technical agencies. Conclusion. This study concludes that the success of public service digitalization requires a stable national system, enhanced staff capacity, and ongoing public support.